Adjuvant zoledronic acid therapy for postmenopausal women with early breast cancer in China: a cost-effectiveness analysis - Huang, Xiaoting; Liu, Yiwei; Lin, Shen; Wang, Hang; Deng, Yujie; Rao, Xin; Guo, Xianzhong; Jiang, Xinchan; Weng, Xiuhua; Huang, Pinfang (International journal for quality in health care, 2023)
Abstract Combination therapy of zoledronic acid (ZOL) plus aromatase inhibitor (AI) was found to reduce bone metastasis risk and improve overall survival for treatment-naïve postmenopausal women (PMW) with hormone receptor–positive (HR+) early breast cancer (EBC), when compared with AI alone. The objective of this study was to evaluate the cost-effectiveness of adding ZOL to AI in treating PMW with HR+ EBC in China. A 5-state Markov model was constructed to evaluate the cost-effectiveness of adding ZOL to AI for PMW-EBC (HR+) over a lifetime horizon from the perspective of Chinese healthcare provider. Data used were obtained from previous reports and public data. The primary outcomes of this study were direct medical cost, life years (LYs), quality-adjusted LYs (QALYs), and incremental cost-effectiveness ratios (ICERs). One-way and probabilistic sensitivity analyses were performed to examine the robustness of the presented model. Over a lifetime horizon, adding ZOL to AI was projected to yield a gain of 1.286 LYs and 1.099 QALYs compared with AI monotherapy, which yielded ICER $11 140.75 per QALY with an incremental cost of $12 247.36. The one-way sensitivity analysis indicated that the cost of ZOL was the most influential factor in our study. The probability that adding ZOL to AI was cost-effective at a threshold of $30 425 per QALY in China was 91.1%. ZOL is likely to be cost-effective in reducing bone metastasis risk and improving overall survival for PMW-EBC (HR+) in China.